Inovasi Media Pembelajaran PAI Berbasis Digital untuk Meningkatkan Motivasi Belajar Siswa - Rizka Arianti (PT. Nawa Edukasi Nusantara, 2025)
This study aims to examine the innovative forms of digital-based Islamic Religious Education (PAI) learning media and analyze their influence on students' learning motivation. This study uses a library research method with a descriptive qualitative approach. Data was obtained through literature review from scientific journals, books, and documents relevant to the theme of digital learning and learning motivation. The results of the analysis show that digital media such as animated videos, educational Android applications, Learning Management System (LMS), and social media based on Islamic content are able to increase student involvement and interest in PAI learning. This media is able to create an interactive, interesting, and learning atmosphere in accordance with the characteristics of the digital generation. Because this media is considered more in accordance with the characteristics of the digital generation which tends to be visual and interactive. However, the success of its implementation is greatly influenced by supporting factors such as teacher competence and adequate infrastructure, and is constrained by the limitations of teachers' digital literacy and inequality of access to technology. This study recommends improving teacher training, digital Islamic content development, and school policies that support innovation as strategies to optimize the use of digital media in PAI learning.